Degradable heat shrinkable film and preparation method thereof
By adopting a three-layer film structure, the degradable heat shrink film is used to use the combination of corn starch modifier and degradation masterbatch, the problem of poor degradation performance of existing heat shrink film materials is solved, and higher environmental protection and mechanical properties are achieved. At the same time, rapid degradation is achieved after use, reducing environmental pollution.
Patent Information
- Application Number
- CN202411875678.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The degradation performance of existing heat shrink film materials is poor, resulting in environmental pollution. The application of biodegradable materials in heat shrink films is limited by production costs and processing characteristics, which affects the heat shrinkage effect and mechanical strength of the film.
The degradable heat shrinkable film adopts a three-layer film structure, the upper and lower films use LDPE, MLLDPE or HDPE, and the middle film consists of a degradation masterbatch and a corn starch modifier. The corn starch modifier includes corn starch, polyvinyl alcohol, vegetable protein fibers and natural polymers, and the degradation masterbatch includes polyethylene powder, peroxide, metal salts and stabilizers.
It achieves better environmental protection performance, stronger degradability and more balanced mechanical properties, maintains the excellent performance of the heat shrink film, and at the same time, rapidly degrading after use, reducing the burden on the environment.
Smart Images

Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thin films, and in particular to a degradable heat shrinkable film and a preparation method thereof. Background Art
[0002] Most heat shrink films are made of petroleum-based plastics such as polyethylene (PE), polyvinyl chloride (PVC), and polypropylene (PP), which have poor degradability. They need to undergo a long-term degradation process in the environment, and the degradation process is relatively slow, which will cause a greater burden on the environment.
[0003] The degradation performance of heat shrink film is closely related to its structural characteristics. In order to ensure that the film can shrink smoothly and maintain its strength during heating, some polymers with strong stability are usually required. Due to the high density and low air permeability of heat shrink film, the degradation rate of conventional heat shrink film is relatively slow, especially polyethylene and polypropylene materials, which often remain in the soil or ocean for hundreds of years without appropriate external conditions (such as ultraviolet rays, oxygen, moisture, etc.).
[0004] In order to meet the application requirements of heat shrink film, the film material needs to have high strength, toughness and heat resistance, which usually rely on petroleum-based materials, which perform poorly in terms of degradation. For example, PVC (polyvinyl chloride), a common heat shrink film material, releases harmful chlorides during its degradation process, which is not only harmful to the environment, but also makes its degradability more complicated.
[0005] At present, although some biodegradable materials (such as PLA, PHA, etc.) can replace traditional petroleum-based plastics, the shrinkage properties of these materials are usually poor and the production cost is high. Therefore, the use of these materials in heat shrink film will affect the heat shrinkage effect and mechanical strength of the film. Moreover, in the production process of heat shrink film, it is usually necessary to achieve the shrinkage of the film through heating, stretching, cooling and other steps. These processes have high requirements for the selection of materials and processing methods, and biodegradable plastics usually do not have the same processing characteristics as traditional plastics. Biodegradable plastics are usually weak and cannot withstand high temperature and high pressure environments. Therefore, in the application of heat shrink film, their stability and durability cannot be comparable to traditional heat shrink film. For example, the processing temperature and fluidity of biodegradable plastics such as PLA are quite different from those of traditional plastics, which may make it impossible for them to achieve the shrinkage effect smoothly in the actual production process. Summary of the invention
[0006] In view of the defects of the prior art, the purpose of the present invention is to provide a degradable heat shrinkable film and a preparation method thereof to solve the problems raised in the above background technology.
[0007] The present invention solves the technical problem by adopting the following technical solution:
[0008] A degradable heat shrinkable film, comprising an upper film, a middle film and a lower film, wherein the upper film and the lower film comprise one or more of LDPE, MLLDPE and HDPE, and the middle film comprises 80-90 parts of a degradation masterbatch and 10-20 parts of a corn starch modifier;
[0009] The corn starch modifier includes corn starch, polyvinyl alcohol, plant protein fiber, and natural polymer;
[0010] The degradation masterbatch comprises polyethylene powder, peroxide, metal salt and stabilizer.
[0011] Preferably, the corn starch modifier comprises 50-60% corn starch, 30-35% polyvinyl alcohol, 5-8% plant protein fiber, and 5-8% natural polymer.
[0012] Preferably, the plant protein fiber is one or more of soybean protein fiber, wheat protein fiber, seaweed protein fiber, and corn protein fiber;
[0013] The natural polymer is one or more of gelatin, alginate and cellulose.
[0014] Preferably, the degradation masterbatch comprises 70-80% polyethylene powder, 5-10% peroxide, 10-20% metal salt, and 1-3% stabilizer;
[0015] The peroxide includes one or more of benzoyl peroxide, dibenzoyl peroxide, cyclohexyl peroxide, diisophorone peroxide, and methyl peroxide;
[0016] The metal salt includes one or more of ferric chloride, ferric sulfate, copper sulfate, copper chloride, and copper acetate;
[0017] The stabilizer is one or more of sulfite, nitrite, sodium molybdate and sodium dihydrogen phosphate.
[0018] In addition, the present application also provides a method for preparing the above-mentioned degradable heat shrinkable film, comprising the following steps:
[0019] S1: drying one or more of LDPE, MLLDPE, HDPE, degradation masterbatch, and corn starch modifier;
[0020] S2: adding the raw materials of the upper film and the lower film into the first screw extruder and the third screw extruder respectively, melting them to obtain an upper melt and a lower melt;
[0021] S3: adding the raw materials of the middle layer film into the second screw extruder for melting to obtain a middle layer melt;
[0022] S4: using a co-extrusion die head to fuse the upper melt, the middle melt, and the lower melt together to form a multi-layer composite structure;
[0023] S5: The coextruded melt is formed into a film through a die head, and then cooled, stretched, and heat-set to obtain a degradable heat shrinkable film.
[0024] Preferably, the preparation method of the corn starch modifier comprises the following steps:
[0025] S11: dissolving the plant protein in 40% glacial acetic acid solution, and adjusting the pH value of the solution to 1.5-2.0 to obtain a protein solution;
[0026] S12: stirring the protein solution at 80-100° C. for 4-6 hours to obtain a protein fiber solution, and spray-drying the protein fiber solution to obtain plant protein fibers;
[0027] S13: corn starch, polyvinyl alcohol, plant protein fiber and natural polymer are fully stirred at -4°C, and then the corn starch modifier particles are formed by a kneading machine.
[0028] Preferably, the method for preparing the degradation masterbatch comprises the following steps:
[0029] S21: After the polyethylene powder, peroxide, metal salt and stabilizer are fully mixed and uniformly, a cold granulator is used at 30-80°C to prepare degradation masterbatch particles.
[0030] Preferably, in step S2, the feeding zone temperature of the first screw extruder and the third screw extruder is 160-180°C, the melting zone temperature is 180-220°C, the mixing zone temperature is 200-230°C, and the die head temperature is 220-240°C.
[0031] Preferably, in step S2, the temperature of the feeding zone of the second screw extruder is 30-60°C, the temperature of the melting zone is 100-130°C, the temperature of the mixing zone is 130-150°C, and the temperature of the die head is 140-160°C.
[0032] Preferably, the stretching ratio of the cooling and stretching treatment in step S5 is 2:1-5:1, the cooling temperature is 40-60°C, the stretching temperature is 60-80°C, the cooling rate is 10-30°C / s, and the heat setting temperature is 100-140°C.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) Compared with existing heat shrinkable films and degradable films, the degradable heat shrinkable film of the present application has better environmental performance, stronger degradability and more balanced mechanical properties. Through the synergistic effect of the biodegradation of the corn starch modifier and the chemical degradation of the degradation masterbatch, the excellent performance of the heat shrinkable film can be maintained, and it can also be quickly degraded after use, reducing the burden on the environment;
[0035] (2) The corn starch modifier in the present application is a composite of corn starch, polyvinyl alcohol, plant protein fiber and natural polymer, which can improve the mechanical properties of the film while enhancing the degradability and biocompatibility of the film; polyvinyl alcohol enhances the water solubility of the film, making the film easier to degrade in a humid environment; plant protein fiber provides enhanced mechanical properties for the film, improves the flexibility and tensile strength of the film, and makes the film less likely to break or deform during heat shrinkage; natural polymers can improve the flexibility and crack resistance of the film, help improve the ductility of the film, and make the film less likely to break when stretched, thereby enhancing the toughness and tensile strength of the film during use; corn starch, plant protein fiber and natural polymers can be degraded under the action of microorganisms, which helps to improve the biodegradability of the film material, so that the film can be decomposed more quickly after use, thereby reducing the environmental burden of plastic waste.
[0036] (3) The peroxide degradation accelerator added to the degradation masterbatch can cause the membrane material to degrade by initiating a free radical reaction. Peroxide can decompose and release free radicals under heat and light conditions, thereby initiating the breakage of the polymer chain, gradually destroying the structure of the membrane and reducing its service life. The addition of metal salts helps to accelerate the degradation process and promote the degradation of the membrane material in the soil or compost environment, while the stabilizer can prevent the peroxide from decomposing and releasing free radicals during the processing process, and maintain the stability of the membrane during use;
[0037] (4) Preparation of corn starch modifier: Acid denaturation is used to "unfold" the plant protein molecules from their original tight structure, preparing for the subsequent formation of a fiber structure. After the protein is denatured in an acidic environment, it has better solubility and can be more evenly dispersed in the system; high-temperature heat treatment causes chemical cross-linking and polymerization reactions between protein molecules to form relatively tough protein fibers, improving the plasticity and stability of plant protein, allowing it to form structured fibers in subsequent steps, which not only improves the physical properties of plant protein, but also helps its compatibility with other components in subsequent processing; low-temperature stirring can avoid uneven reaction or thermal decomposition caused by temperature increase during stirring, which helps to maintain the characteristics of each component during the mixing process and improves the compatibility between corn starch, polyvinyl alcohol, plant protein fibers and natural polymers, thereby improving the uniformity of the final particles. DETAILED DESCRIPTION
[0038] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The upper film and the lower film described in the present application are films disposed on both sides of the middle film, not specifically referring to the inner layer and the outer layer, and the inner and outer layers can be adjusted according to packaging requirements.
[0040] Example 1
[0041] A degradable heat shrinkable film, comprising an upper film, a middle film and a lower film, wherein:
[0042] The upper film and the lower film include the following components in parts by weight: 60 parts of LDPE, 27 parts of MLLDPE, and 13 parts of HDPE.
[0043] The middle layer film has the following components in parts by weight: 85 parts of degradation masterbatch, 15 parts of corn starch modifier;
[0044] The corn starch modifier includes 50% corn starch, 35% polyvinyl alcohol, 8% soybean protein fiber and 7% gelatin in weight percentage.
[0045] The degradation masterbatch comprises 75% by weight of polyethylene powder, 3% of benzoyl oxide, 4% of dibenzoyl peroxide, 10% of ferric chloride, 5% of copper sulfate, 2% of sulfite and 1% of sodium molybdate.
[0046] The method for preparing a degradable heat shrinkable film comprises the following steps:
[0047] S1: Dry LDPE, MLLDPE, HDPE, degradation masterbatch and corn starch modifier at 30-40°C for 5-8h;
[0048] S2: adding the raw materials of the upper film and the lower film to the first screw extruder and the third screw extruder respectively, melting them to obtain the upper melt and the lower melt, the feeding zone temperature of the first screw extruder and the third screw extruder is 170-180°C, the melting zone temperature is 190-200°C, the mixing zone temperature is 210-220°C, and the die head temperature is 220-230°C;
[0049] S3: adding the raw materials of the middle layer film into the second screw extruder for melting to obtain a middle layer melt; the feeding zone temperature of the second screw extruder is 30-40°C, the melting zone temperature is 100-110°C, the mixing zone temperature is 120-130°C, and the die head temperature is 140-150°C;
[0050] S4: Using a co-extrusion die head, the upper melt, the middle melt, and the lower melt are fused together to form a multi-layer composite structure, the thickness of the upper melt and the lower melt is 75 μm, and the thickness of the middle melt is 30 μm;
[0051] S5: The co-extruded melt is formed into a film through a die head, and then cooled, stretched and heat-set to obtain a degradable heat shrinkable film. The transverse stretching ratio of the cooling and stretching treatment is 4:1, the longitudinal stretching ratio is 3:1, the cooling temperature is 40-50°C, the stretching temperature is 60-70°C, the cooling rate is 15°C / s, and the heat setting is 120°C.
[0052] In this embodiment, the preparation method of the corn starch modifier comprises the following steps:
[0053] S11: dissolving soybean protein in 40% glacial acetic acid solution, and adjusting the pH value of the solution to 1.5 to obtain a protein solution;
[0054] S12: stirring the protein solution at 80° C. for 5 hours to obtain a soybean protein fiber solution, and spray-drying the protein fiber solution to obtain soybean protein fiber;
[0055] S13: corn starch, polyvinyl alcohol, soybean protein fiber and gelatin are fully stirred at -4°C, and then formed into 0.2 mm granules of corn starch modifier using a kneader.
[0056] The preparation method of the degradation masterbatch comprises the following steps:
[0057] S21: After polyethylene powder, benzoyl peroxide, dibenzoyl peroxide, ferric chloride, copper sulfate, sulfite and sodium molybdate are fully mixed and uniformly mixed, a cold granulator is used at 70-80° C. to prepare degradation masterbatch particles.
[0058] Example 2
[0059] A degradable heat shrinkable film, comprising an upper film, a middle film and a lower film, wherein:
[0060] The upper film and the lower film include the following components in parts by weight: 100 parts of LDPE.
[0061] The middle layer film has the following components in parts by weight: 80 parts of degradation masterbatch, 20 parts of corn starch modifier;
[0062] The corn starch modifier comprises 60% corn starch, 30% polyvinyl alcohol, 5% soybean protein fiber and 5% sodium alginate in weight percentage.
[0063] The degradation masterbatch comprises 80% by weight of polyethylene powder, 3% of cyclohexyl peroxide, 2% of methyl peroxide, 10% of ferric chloride, 5% of cupric acetate, 2% of nitrite and 1% of sodium dihydrogen phosphate.
[0064] The method for preparing a degradable heat shrinkable film comprises the following steps:
[0065] S1: Dry LDPE, degradation masterbatch and corn starch modifier at 30-40°C for 5-8h;
[0066] S2: adding the raw materials of the upper film and the lower film into the first screw extruder and the third screw extruder respectively, melting them to obtain the upper melt and the lower melt, the feeding zone temperature of the first screw extruder and the third screw extruder is 160-170°C, the melting zone temperature is 180-190°C, the mixing zone temperature is 190-200°C, and the die head temperature is 200-210°C;
[0067] S3: adding the raw materials of the middle layer film into the second screw extruder for melting to obtain a middle layer melt; the feeding zone temperature of the second screw extruder is 30-40°C, the melting zone temperature is 100-110°C, the mixing zone temperature is 120-130°C, and the die head temperature is 140-150°C;
[0068] S4: Using a co-extrusion die head, the upper melt, the middle melt, and the lower melt are fused together to form a multi-layer composite structure, the thickness of the upper melt and the lower melt is 75 μm, and the thickness of the middle melt is 30 μm;
[0069] S5: The co-extruded melt is formed into a film through a die head, and then cooled, stretched and heat-set to obtain a degradable heat shrinkable film. The transverse stretching ratio of the cooling and stretching treatment is 5:1, the longitudinal stretching ratio is 4:1, the cooling temperature is 40-50°C, the stretching temperature is 60-70°C, the cooling rate is 15°C / s, and the heat setting is 110°C.
[0070] In this embodiment, the preparation method of the corn starch modifier comprises the following steps:
[0071] S11: dissolving soybean protein in 40% glacial acetic acid solution, and adjusting the pH value of the solution to 1.5 to obtain a protein solution;
[0072] S12: stirring the protein solution at 80° C. for 5 hours to obtain a soybean protein fiber solution, and spray-drying the protein fiber solution to obtain soybean protein fiber;
[0073] S13: corn starch, polyvinyl alcohol, soybean protein fiber and sodium alginate are fully and uniformly stirred at -4°C, and then a kneader is used to form corn starch modifier particles of 0.2 mm in size.
[0074] The preparation method of the degradation masterbatch comprises the following steps:
[0075] S21: After polyethylene powder, cyclohexyl peroxide, methyl peroxide, ferric chloride, cupric acetate, sulfite and sodium dihydrogen phosphate are fully mixed and uniformly mixed, a cold granulator is used at 70-80°C to prepare degradation masterbatch particles.
[0076] Example 3
[0077] A degradable heat shrinkable film, comprising an upper film, a middle film and a lower film, wherein:
[0078] The upper film comprises the following components in parts by weight: 60 parts of LDPE, 27 parts of MLLDPE, and 13 parts of HDPE;
[0079] The lower film includes the following components in parts by weight: 50 parts of MLLDPE and 50 parts of HDPE;
[0080] The middle layer film has the following components in parts by weight: 90 parts of degradation masterbatch, 10 parts of corn starch modifier;
[0081] The corn starch modifier comprises 54% corn starch, 30% polyvinyl alcohol, 6% wheat protein fiber, 2% seaweed protein fiber, 2% sodium alginate and 6% gelatin in weight percentage.
[0082] The degradation masterbatch comprises 80% by weight of polyethylene powder, 2% of benzoyl oxide, 3% of dibenzoyl peroxide, 8% of ferric sulfate, 2% of copper sulfate and 1% of sodium molybdate.
[0083] The method for preparing a degradable heat shrinkable film comprises the following steps:
[0084] S1: Dry LDPE, MLLDPE, HDPE, degradation masterbatch and corn starch modifier at 30-40°C for 5-8h;
[0085] S2: adding the raw materials of the upper film and the lower film into the first screw extruder and the third screw extruder respectively, melting them to obtain the upper melt and the lower melt, the feeding zone temperature of the first screw extruder is 170-180°C, the melting zone temperature is 190-200°C, the mixing zone temperature is 210-220°C, and the die head temperature is 230-240°C;
[0086] The feeding zone temperature of the third screw extruder is 170-180°C, the melting zone temperature is 210-220°C, the mixing zone temperature is 220-230°C, and the die head temperature is 230-240°C;
[0087] S3: adding the raw materials of the middle layer film into the second screw extruder for melting to obtain a middle layer melt; the feeding zone temperature of the second screw extruder is 40-50°C, the melting zone temperature is 110-120°C, the mixing zone temperature is 130-140°C, and the die head temperature is 150-160°C;
[0088] S4: Using a co-extrusion die head, the upper melt, the middle melt, and the lower melt are fused together to form a multi-layer composite structure, the thickness of the upper melt and the lower melt is 75 μm, and the thickness of the middle melt is 30 μm;
[0089] S5: The co-extruded melt is formed into a film through a die head, and then cooled, stretched and heat-set to obtain a degradable heat shrinkable film. The transverse stretching ratio of the cooling and stretching treatment is 4:1, the longitudinal stretching ratio is 3:1, the cooling temperature is 40-50°C, the stretching temperature is 60-70°C, the cooling rate is 15°C / s, and the heat setting is 120°C.
[0090] In this embodiment, the preparation method of the corn starch modifier comprises the following steps:
[0091] S11: dissolving wheat protein and seaweed protein in 40% glacial acetic acid solution, respectively, and adjusting the pH values of the solutions to 1.5 and 2, respectively, to obtain wheat protein solution and seaweed protein solution;
[0092] S12: stirring the wheat protein solution at 100° C. for 4 hours to obtain a wheat protein fiber solution, stirring the seaweed protein solution at 80° C. for 5 hours to obtain a seaweed protein fiber solution, and spray-drying the wheat protein fiber solution and the seaweed protein fiber solution to obtain wheat protein fiber and seaweed protein fiber, respectively;
[0093] S13: corn starch, polyvinyl alcohol, wheat protein fiber, seaweed protein fiber, sodium alginate and gelatin are fully and uniformly stirred at -4°C, and then a kneader is used to form corn starch modifier particles of 0.2 mm in size.
[0094] The preparation method of the degradation masterbatch comprises the following steps:
[0095] S21: After the polyethylene powder, benzoyl peroxide, dibenzoyl peroxide, dibenzoyl peroxide, ferric sulfate, copper sulfate and sodium molybdate are fully mixed and uniformly mixed, a degradation masterbatch pellet is prepared at 70-80° C. using a cold granulator.
[0096] Example 4
[0097] A degradable heat shrinkable film, comprising an upper film, a middle film and a lower film, wherein:
[0098] The upper film includes the following components in parts by weight: 100 parts of MLLDPE;
[0099] The lower film includes the following components in parts by weight: 100 parts of HDPE;
[0100] The middle layer film has the following components in parts by weight: 90 parts of degradation masterbatch, 10 parts of corn starch modifier;
[0101] The corn starch modifier comprises 50% corn starch, 35% polyvinyl alcohol, 5% seaweed protein fiber, 2% corn protein fiber, 3% gelatin and 5% cellulose in weight percentage.
[0102] The degradation masterbatch comprises 70% by weight of polyethylene powder, 7% of dibenzoyl peroxide, 3% of diisophorone peroxide, 10% of ferric chloride, 7% of copper sulfate, 2% of sulfite and 1% of sodium molybdate.
[0103] The method for preparing a degradable heat shrinkable film comprises the following steps:
[0104] S1: Dry MLLDPE, HDPE, degradation masterbatch and corn starch modifier at 30-40°C for 5-8h;
[0105] S2: adding the raw materials of the upper film and the lower film into the first screw extruder and the third screw extruder respectively, melting them to obtain the upper melt and the lower melt, the feeding zone temperature of the first screw extruder is 170-180°C, the melting zone temperature is 190-200°C, the mixing zone temperature is 210-220°C, and the die head temperature is 230-240°C;
[0106] The feeding zone temperature of the third screw extruder is 170-180°C, the melting zone temperature is 210-220°C, the mixing zone temperature is 220-230°C, and the die head temperature is 230-240°C;
[0107] S3: adding the raw materials of the middle layer film into the second screw extruder for melting to obtain a middle layer melt; the feeding zone temperature of the second screw extruder is 50-60°C, the melting zone temperature is 120-130°C, the mixing zone temperature is 140-150°C, and the die head temperature is 150-160°C;
[0108] S4: Using a co-extrusion die head, the upper melt, the middle melt, and the lower melt are fused together to form a multi-layer composite structure, the thickness of the upper melt and the lower melt is 75 μm, and the thickness of the middle melt is 30 μm;
[0109] S5: The co-extruded melt is formed into a film through a die head, and then cooled, stretched and heat-set to obtain a degradable heat shrinkable film. The transverse stretching ratio of the cooling and stretching treatment is 3:1, the longitudinal stretching ratio is 2:1, the cooling temperature is 50-60°C, the stretching temperature is 70-80°C, the cooling rate is 30°C / s, and the heat setting is 140°C.
[0110] In this embodiment, the preparation method of the corn starch modifier comprises the following steps:
[0111] S11: dissolving seaweed protein and corn protein in 40% glacial acetic acid solution, and adjusting the pH value of the solution to 2 to obtain a protein solution;
[0112] S12: stirring the protein solution at 80° C. for 5 h to obtain seaweed protein fiber and corn protein fiber solutions, and spray drying the protein fiber solutions to obtain seaweed protein fiber and corn protein fiber;
[0113] S13: corn starch, polyvinyl alcohol, seaweed protein fiber, corn protein fiber and gelatin are fully stirred at -4°C, and after stirring, 0.2 mm corn starch modifier particles are formed using a kneader.
[0114] The preparation method of the degradation masterbatch comprises the following steps:
[0115] S21: After polyethylene powder, dibenzoyl peroxide, diisophorone peroxide, ferric chloride, copper sulfate, sulfite and sodium molybdate are fully mixed and uniformly mixed, a cold granulator is used at 70-80°C to prepare degradation masterbatch particles.
[0116] Comparative Example 1
[0117] The difference between this comparative example and Example 1 is that no corn starch modifier is used, and an equal amount of degradation masterbatch is used instead.
[0118] Comparative Example 2
[0119] The difference between this comparative example and Example 1 is that an equal amount of corn starch is used to replace the corn starch modifier.
[0120] Comparative Example 3
[0121] The difference between this comparative example and Example 1 is that the corn starch modifier does not include plant protein fiber, and an equal amount of corn starch is used instead.
[0122] Comparative Example 4
[0123] The difference between this comparative example and Example 1 is that the corn starch modifier does not include a natural polymer, and an equal amount of corn starch is used instead.
[0124] Comparative Example 5
[0125] The difference between this comparative example and Example 1 is that the corn starch modifier does not include polyvinyl alcohol, and an equal amount of corn starch is used instead.
[0126] Comparative Example 6
[0127] The difference between this comparative example and Example 1 is that the corn starch modifier does not include polyvinyl alcohol, and an equal amount of polylactic acid is used instead.
[0128] Comparative Example 7
[0129] The difference between this comparative example and Example 1 is that no degradation masterbatch is used, and an equal amount of corn starch modifier is used.
[0130] Comparative Example 8
[0131] The difference between this comparative example and Example 1 is that the degradation masterbatch does not include peroxide, metal salt and stabilizer, and an equal amount of polyethylene powder is used instead.
[0132] Comparative Example 9
[0133] The difference between this comparative example and Example 1 is that the degradation masterbatch does not include a stabilizer, and an equal amount of polyethylene powder is used instead.
[0134] Comparative Example 10
[0135] The difference between this comparative example and Example 1 is that in step S2, the feeding zone temperature of the second screw extruder is 20-30°C, the melting zone temperature is 90-100°C, the mixing zone temperature is 120-130°C, and the die head temperature is 130-140°C.
[0136] Comparative Example 11
[0137] The difference between this comparative example and Example 1 is that the transverse stretching ratio of the cooling and stretching treatment in S5 is 6:1, the longitudinal stretching ratio is 3:1, the cooling temperature is 30-40°C, the stretching temperature is 50-60°C, the cooling rate is 8°C / s, and the heat setting temperature is 100-140°C.
[0138] Comparative Example 12
[0139] The difference between this comparative example and Example 1 is that in the preparation method of the corn starch modifier, the pH of the protein solution is adjusted to 3 in S11.
[0140] Comparative Example 13
[0141] The difference between this comparative example and Example 1 is that in the preparation method of the corn starch modifier, in S12, the protein solution is stirred at 110° C. for 5 h.
[0142] Comparative Example 14
[0143] The difference between this comparative example and Example 1 is that in the preparation method of the corn starch modifier, in S12, the protein solution is stirred at 70° C. for 4-6 hours.
[0144] Comparative Example 15
[0145] The difference between this comparative example and Example 1 is that in the preparation method of the degradation masterbatch, in S21, the polyethylene powder, peroxide, metal salt and stabilizer are fully mixed and then made into degradation masterbatch particles at 100-110° C. using a cold granulator.
[0146] Comparative Example 16
[0147] The difference between this comparative example and Example 1 is that there is only a middle layer film, and the thickness of the prepared middle layer melt is 180 μm.
[0148] Test items
[0149] (1) Tensile strength
[0150] According to ASTM D882, the specimens are of type 2, 150±0.1mm long and 15±0.1mm wide, with a clamp spacing of 100mm and a tensile speed of (100±10)mm / min. Five specimens are tested and the average value is taken.
[0151] (2) Thermal shrinkage
[0152] According to ASTM D1204, place the sample in 90℃ water (try to immerse the surface of the sample at the same time), place it for 10 seconds, take it out and cool it to the test environment temperature, measure the length before and after it is put in, calculate the thermal shrinkage of the sample, test 3 parallels for each group of samples, and take the average value.
[0153] (3) Oxygen permeability
[0154] According to GB / T 1038-2000, the test was carried out using an oxygen permeability tester with a sample size of 10 cm 2 The sample is circular and is glued to the effective test area with a special sealant. Three parallel tests are conducted on each group of samples. After each test, the instrument directly reads the oxygen transmission rate value and takes the average value.
[0155] (4) Water vapor transmission rate
[0156] According to GB / T 26253-2010, the test was carried out using a moisture permeability tester with a sample size of 2 cm. 2 The test specimens are glued to the effective test area with a special sealant. Each group of specimens is tested with 6 parallels. After the test, the instrument directly reads the water vapor transmission rate value and takes the average value.
[0157] (5) Weight loss rate of soil burial degradation
[0158] The biodegradability of the film in the soil at room temperature was evaluated according to ISO 11465. The sample was a 5 cm × 5 cm square and buried in a flower pot with a burial depth of about 5 cm. In order to maintain soil moisture, 10 ml of deionized water was sprayed evenly every day. Before the experiment, the sample was dried at 65 ° C to a constant weight and the mass was recorded as W0. Every 10 days, the sample was taken out, wiped and dried for 2 hours, and the mass W was recorded. n The weight loss rate was calculated according to the following formula. The experiment lasted for 70 days, and the weight loss rate was used to measure the degradation performance of the membrane.
[0159]
[0160] (6) Photodegradation weight loss rate
[0161] The photodegradability of the film was evaluated according to the provisions of ISO 11507. The sample was a 5 cm × 5 cm square and was placed in a UV accelerated aging box. The temperature was maintained at 60 ° C and the relative humidity was 50-70%. Before the experiment, the mass was recorded as W1, and the mass was recorded as W every 24 hours. m The weight loss rate was calculated according to the following formula. The experiment lasted for 240 h, and the degradation performance of the membrane was measured by the weight loss rate.
[0162]
[0163] The test results are shown in Tables 1 and 2.
[0164] Table 1 Test results of Example 1 to Example 5
[0165]
[0166] In the present application, a three-layer membrane structure is adopted. In actual use, the number of membrane layers, the raw materials used for the upper membrane / lower membrane, the thickness of the membrane, etc. can be adjusted according to the requirements of the service life of the membrane.
[0167] Table 2 Test results of Example 1 and Comparative Example 16
[0168]
[0169] It can be seen from the data of Example 1 and the comparative example that the use of corn starch modifier can appropriately improve the shrinkage of the film, and the degradation ability is greatly improved when the film is buried in the soil for degradation. The degradation masterbatch can degrade the film to a certain extent when the film is exposed to sunlight for a long time, and the degradation speed of the film will be accelerated under certain humidity conditions. When the film is buried in the soil, the corn starch modifier plays a major role in degradation. When the corn starch modifier and the degradation masterbatch are combined to ensure the thermal shrinkage performance of the film, the degradation ability of the film is improved.
[0170] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0171] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A degradable heat shrinkable film, characterized in that: It comprises an upper film, a middle film and a lower film, wherein the upper film and the lower film comprise one or more of LDPE, MLLDPE and HDPE, and the middle film comprises 80-90 parts of a degradation masterbatch and 10-20 parts of a corn starch modifier; The corn starch modifier includes corn starch, polyvinyl alcohol, plant protein fiber, and natural polymer; The degradation masterbatch comprises polyethylene powder, peroxide, metal salt and stabilizer; The corn starch modifier comprises 50-60% corn starch, 30-35% polyvinyl alcohol, 5-8% plant protein fiber, and 5-8% natural polymer; The preparation method of the degradable heat shrinkable film comprises: respectively adding raw materials of an upper film, a middle film and a lower film, and forming a film by co-extruding the co-extruded upper melt, middle melt and lower melt through a die head, and then cooling, stretching and heat-setting to obtain a degradable heat shrinkable film; The preparation method of the corn starch modifier comprises the following steps: S11: dissolving the plant protein in 40% glacial acetic acid solution, and adjusting the pH value of the solution to 1.5-2.0 to obtain a protein solution; S12: stirring the protein solution at 80-100° C. for 4-6 hours to obtain a protein fiber solution, and spray-drying the protein fiber solution to obtain plant protein fibers; S13: corn starch, polyvinyl alcohol, plant protein fiber and natural polymer are fully stirred at -4°C, and then formed into corn starch modifier particles by a kneader.
2. The degradable heat shrinkable film according to claim 1, characterized in that: The plant protein fiber is one or more of soybean protein fiber, wheat protein fiber, seaweed protein fiber, and corn protein fiber; The natural polymer is one or more of gelatin, alginate and cellulose.
3. The degradable heat shrinkable film according to claim 1, characterized in that: The degradation masterbatch comprises 70-80% polyethylene powder, 5-10% peroxide, 10-20% metal salt and 1-3% stabilizer; The peroxide includes one or more of benzoyl peroxide, dibenzoyl peroxide, cyclohexyl peroxide, diisophorone peroxide, and methyl peroxide; The metal salt includes one or more of ferric chloride, ferric sulfate, copper sulfate, copper chloride, and copper acetate; The stabilizer is one or more of sulfite, nitrite, sodium molybdate and sodium dihydrogen phosphate.
4. A method for preparing a degradable heat shrinkable film, characterized in that: The method for preparing the degradable heat shrinkable film according to any one of claims 1 to 3 comprises the following steps: S1: drying one or more of LDPE, MLLDPE, HDPE, degradation masterbatch, and corn starch modifier; S2: adding the raw materials of the upper film and the lower film into the first screw extruder and the third screw extruder respectively, melting them to obtain an upper melt and a lower melt; S3: adding the raw materials of the middle layer film into the second screw extruder, melting them, and obtaining a middle layer melt; S4: using a co-extrusion die head to fuse the upper melt, the middle melt, and the lower melt together to form a multi-layer composite structure; S5: The coextruded melt is formed into a film through a die head, and then cooled, stretched, and heat-set to obtain a degradable heat shrinkable film.
5. The method for preparing a degradable heat shrinkable film according to claim 4, characterized in that: The preparation method of the degradation masterbatch comprises the following steps: S21: After the polyethylene powder, peroxide, metal salt and stabilizer are fully mixed and uniformly mixed, a cold granulator is used to make degradation masterbatch particles at 30-80°C.
6. The method for preparing a degradable heat shrinkable film according to claim 4, characterized in that: In step S2, the feeding zone temperature of the first screw extruder and the third screw extruder is 160-180°C, the melting zone temperature is 180-220°C, the mixing zone temperature is 200-230°C, and the die head temperature is 220-240°C.
7. The method for preparing a degradable heat shrinkable film according to claim 6, characterized in that: In step S3, the temperature of the feeding zone of the second screw extruder is 30-60°C, the temperature of the melting zone is 100-130°C, the temperature of the mixing zone is 130-150°C, and the temperature of the die head is 140-160°C.
8. The method for preparing a degradable heat shrinkable film according to claim 6, characterized in that: The stretching ratio of the cooling and stretching treatment in step S5 is 2:1-5:1, the cooling temperature is 40-60°C, the stretching temperature is 60-80°C, the cooling speed is 10-30°C / s, and the heat setting temperature is 100-140°C.
Citation Information
Patent Citations
High-transparency polyethylene heat shrink film and preparation method thereof
CN116728930A
Bioplastics based on amyloid fibrils and biodegradable polymers
CN117597401A